PENGGUNAAN KOHERENSI PADA EDITORIAL TRIBUN PONTIANAK EDISI JUNI 2016 - Meri, Andi; Sulissusiawan, Ahadi; Saman, Sisilya (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research is motivated by the role of coherence in building the integrity of a discourse. The problem discussed in this research is the form of relationship of appointment, relationship of addition, relationship of contradiction, and cause-effect relationship. This research aims to find the forms of coherence used in editorial discourse. The method in this research is descriptive with qualitative research. Data source in this research is editorial Tribun Pontianak Edition June 2016. The data collection technique used is documentary study technique. Data collector the used [is] writer alone and note. The result of analysis of editorial data Tribun Pontianak June 2016 contains the form of coherence in the form of relationship of appointment, relationship addition, relationship of conflict and cause-effect relationship. The relationship of coherence forms is 1137 with details of 645 relations of appointment, 379 additions relationship, 63 contradictory relationships and 50 causal relationships. Forms of coherence at is editorial of Tribun Pontianak Edition June 2016 playing a part in to create perfection of discourseKeywords: Koherensi, Editorial, Wacana